Push, Pull and Mooring Factors on Offline-Online Learning Switching Behavior - Kader Jailani, Sri Fatiany Abdul; Mat Ali, Syukrina Alini; Yunus, Noorain Mohamad; Mozie, Noorizan Mohamad (Information Management and Business Review, 2024)
During the pandemic, many sectors, including education, were affected. The shift from traditional to online learning is an opening for students and educators to explore online learning. Students may connect from anywhere at any time through this learning mode. This sudden shift has impacted the learning behavior of students to a large extent. People can access information anytime and anywhere that is typically available only through a traditional classroom. This study adopts the Push-Pull-Mooring (PPM) theory as the theoretical framework to understand how push, pull, and mooring factors affect students’ shift from offline to online learning. A survey was used as the main instrument in this study. A quantitative approach was utilized to achieve the stated research objectives. The questionnaires were distributed among undergraduate students in public and private schools in Malaysia through convenience sampling techniques. The minimal 77 sample size has been determined by utilizing G*Power software. 117 responses were collected from the questionnaires that met the minimum required sample size for this study. The findings emphasize that push and pull factors are essential to student learning. However, the mooring factor does not affect the student’s switching behavior. The study sheds light on capturing more essential measures in the theoretical development of switching behavior.